Student Teachers' Teaching Skill Development through Mentoring Process - Rozak, Diana Rahmawati (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2014)
This study is about student teachers' basic teaching skills especially in delivering gaining attention, presenting stimulus materials, and assessing performance. The purpose of this study is to find out whether or not student teachers' skill in gaining attention, presenting stimulus materials, and assessing performance was developed during their teaching practice period. To achieve the first purpose, the data were collected through observations and interviews. The observation was conducted during student teachers' teaching-learning sessions. The interview was conducted to support the data from interview. The source for interview was student teachers' mentor teachers. The result of this study was that two of four student teachers had developed their teaching skills in gaining attention while the other two did not develop their skills. This study has showed that besides students' ability, willingness, and support from mentor teachers abd peers are needed to develop their teaching skills.